To Paint a New Picture: Into the Lives of Eldest Siblings of Separated Fami-lies during COVID-19 - Rabuya, Daniel Andrei; Moralde, Franz Elloise; Villacampa, Angel Rose; Sagosa, Shane; Fernandez, Ravyn Bridget; Cabrera, Ralley Kyle; Cagalitan , Willem Mikkel; Bendibel, Rycel Monique; del Socorro, Celeste; Gagani, Flordeliza (Future Science / FSH-PH Publications, 2023)
This study emerged to enable humanitarian organizations to provide better services for children in separated families by understanding eldest siblings' lived experiences. Through Husserlian’s descriptive phenomenology utilizing Colaizzi’s method of data analysis, six participants were interviewed online at the height of the pandemic in 2021-2022 in Cebu City, Philippines. Data were transcribed using data reduction methods and revealed 6 themes: (1)